2015
DOI: 10.4236/jbm.2015.35004
|View full text |Cite
|
Sign up to set email alerts
|

Lead-Induced Damage on Hepatocytes and Hepatic Reticular Fibres in Rats; Protective Role of Aqueous Extract of <i>Moringa oleifera</i> Leaves (Lam)

Abstract: This study was designed to evaluate the hepatoprotective and ameliorative effects of aqueous extract of Moringa oleifera (MO) leaves on the histologyof liver and hepatic reticular fibres integrity of adult Wistar rats following lead-induced hepatotoxicity. Twenty four adult Wistar rats, weighing 180-220 g, randomly assigned into four groups of six animals each were used for the study. Lead and Moringa oleifera were given orally to the rats. 24 hours after the last administration, animals were sacrificed, blood… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 23 publications
1
4
0
Order By: Relevance
“…Significant increase in Catalase activity in fractions of AE-MOL treated group is in accordance with the findings of Omotoso et al, [18] who reported administration of AEMOL with lead afford significant increase in catalase activitiy.…”
Section: In Vivo Free Radical Scavenging Activitysupporting
confidence: 91%
“…Significant increase in Catalase activity in fractions of AE-MOL treated group is in accordance with the findings of Omotoso et al, [18] who reported administration of AEMOL with lead afford significant increase in catalase activitiy.…”
Section: In Vivo Free Radical Scavenging Activitysupporting
confidence: 91%
“…Due to the regulation of reticular fibers (reticulin), it has a branched and network‐like structure, often called a reticulum. These fibers are necessarily type III collagen fibrils (Jobson et al, 2015; Omotoso, Abiodun, Ijomone, & Adewole, 2015; Wiki, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…This is also considered as "Miracle tree" and its leaves hold hepatoprotective, anti-inflammatory, antihypertensive and antimicrobial activities 9 . The leaves of this miraculous plant are rich in antioxidants (SOD and Catalase) phenols, flavonoids and caretenoids 10 , which imparts to its hepatoprotective potential Therapy with Mo leaves reduces the liver damage and promotes regeneration 11 , this may be associated with the preventive and preserving potential of Moringa oleifera on plasmalemma and increased protein synthesis. These leaves possess combination of calcium, iron, protein, carbohydrates, copper and vitamins are helpful in lowering blood pressure and glucose levels and exhibit anti-ulcer and anti-inflammatory effect.…”
Section: Introductionmentioning
confidence: 99%